MinD-dependent conformational changes in MinE required for the Min oscillator to spatially regulate cytokinesis - Park, Kyung-Tae (2011)
MinD recruits MinE to the membrane leading to a coupled oscillation required for spatial regulation of the cytokinetic Z ring in E. coli. How these proteins interact, however, is not clear since the MinD binding regions of MinE are sequestered within a 6-stranded β-sheet and masked by N-terminal helices. Here, minE mutations are isolated that restore interaction to some MinD and MinE mutants. These mutations alter the MinE structure releasing the MinD binding regions and N-terminal helices that bind MinD and the membrane, respectively. Crystallization of MinD-MinE complexes reveals a 4-stranded β-sheet MinE dimer with the released β strands (MinD binding regions) converted to α-helices bound to MinD dimers. These results suggest a 6 stranded, β-sheet dimer of MinE ‘senses’ MinD and switches to a 4-stranded β-sheet dimer that binds MinD and contributes to membrane binding. Also, the results indicate how MinE persists at the MinD-membrane surface.